Molecular characterization of avian influenza virus isolate VRI1803/04 and development of real-time rt-pcr detection method - Zulkifli, Hazalina (2013)
Influenza virus can be divided into 3 subtypes; Influenza type A, B and C which belong to the Orthomyxoviridae family. Only influenza type A virus is responsible for infection in avian species. It is divided into low pathogenic avian influenza (LPAI) and highly pathogenic avian influenza (HPAI). Since 2003, outbreaks of HPAI strain H5N1 have occurred in poultry in Asia, Europe, and Africa. Human infections with this subtype have been reported and continued to occur. The ongoing transmission of avian influenza A virus strain H5N1 in Asia and Africa has raised global awareness of the threat of a new influenza pandemic which causes devastating economic lost in poultry industry. It has stimulated interests in the development of a rapid laboratory method for detection of influenza A viruses to reduce the time taken as compared to the conventional virus isolation methods. An isolate of AIV designated as VRI1803/04 obtained from Veterinary Research Institute, Ipoh, Perak, Malaysia was used for identification and characterization using the conventional polymerase chain reaction (PCR). The complete sequence of the H and N genes of VRI1803/04 was determined. A total of 1701 and 1410 bp of H and N, respectively, were identified. The H gene has 89% homology to H3 gene from A/duck/Ukraine/1/63 (H3N8). Meanwhile, the N gene has 92% homology to N2 gene from A/Pekin duck/Singapore/F59/04/98 (H5N2). Thus, the VRI1803/04 can be subtyped as H3N2. The complete nucleotide sequence of H gene demonstrated that the VRI1803/04 virus isolate belongs to LPAI due to the absence of multiple basic amino acids in H cleavage sites. Further study was carried out for AIV detection. This assay known as one step real-time RT-PCR universal assay was developed using cheaper dye which is SYBR Green 1. The time taken to complete the whole process was around 6 hours, starting from RNA extraction from the sample until result is obtained, whether the sample contains AI virus or not. The result can be monitored in computer by looking at the existence of amplification curves. The melting temperature peak could be observed as soon as the test was completed. The melting temperature average of the positive amplification product is 83.4 ± 0.6oC using the universal NP primer. The detection limit of the assay was determined by performing serial dilution of total RNA and determination of HA titer. The detection limit for universal assay was 0.1 ng of total RNA and 0.1 HAU. In conclusion, the developed assay offers a rapid method for detection of AIV in a single tube reaction. This technique was used to detect presence of avian influenza virus in poultry samples during HPAI H5N1 outbreak in 2004.